Julian A. McPhee's convocation, 1964 (1964)
[00:00:01] President McPhee greets the students, faculty, and guests [00:01:24] He speaks to his experiences as an undergraduate [00:01:57] He tells the students he is extremely proud of them [00:02:43] Cal Poly students know what they want to accomplish [00:03:51] He asks the students to consider the question, 'Why are you here?' [00:04:00] He then gives several reasons as to why they would want to be at Cal Poly [00:05:01] He hopes that all the incoming students will enjoy Cal Poly and become supporters [00:05:33] He likes to have these convocations to get in contact with the students and faculty [00:06:21] He encourages the freshman to stick it out for a couple of weeks to get acquainted with the campus [00:06:47] Many students went to the War and came back to Cal Poly instead of going home [00:07:08] Some students stay 7-9 years before graduating because they love Cal Poly that much [00:07:34] He encourages students and faculty to allows smile because that is what makes Cal Poly a friendly campus [00:08:10] Cal Poly Alumni still remember McPhee's convocations and the rules he stated [00:08:28] He wants students to address any issues with the rules and explains how they can change them [00:09:06] When McPhee came to Cal Poly in 1933, there was only one campus with 125 students [00:09:24] In 1964, Cal Poly is now represented by three campuses [00:11:40] He explains that the faculty are going worldwide to get in contact with other programs [00:12:57] Cal Poly was established as a polytechnic college to tailor them for specific occupations [00:13:50] He explains the 'Learn by Doing' standard and how that relates to the 'Upside Down' curriculum [00:14:12] He describes the importance and uniqueness of the relationship students and faculty have [00:14:30] The Cal Poly plan adds the 'know how' to the 'know why' [00:15:50] McPhee asks, 'What is a good citizen?' [00:16:19] As citizens, we should care about the social and economical issues [00:16:59] McPhee encourages the students to participate and get involved in clubs and the community [00:18:18] Cal Poly students are the future [00:20:54] He says that Cal Poly's training for citizenship has been one of the first Cal Poly objectives [00:22:12] McPhee says its important to be good leaders, but to also be able to follow good leadership [00:22:45] He stresses the importance of writing out reports properly for employers [00:23:00] Cal Poly strives to have the best teachers in the faculty staff [00:24:15] He states the importance of respecting others [00:26:08] He discusses the facility work that is occurring on campus [00:26:57] He is hopeful that the student union will be finished [00:27:14] He wants students to keep in mind the importance of perseverance and the use of their time [00:28:34] McPhee closes with his best wishes for a happy and successful year